Energy balance of biodiesel production from rapeseed in Western Australia - Rustandi, Ferry (Curtin University, 2009)
Increasing energy consumption in Australian transport sector, rapidly depleting amount of Australian oil reserves, and the environmental concerns that arise from the associated greenhouse gas emissions produced by the combustion of large amount of fossil fuels during transport activities have increased the interest in using renewable transport fuels, especially ethanol and biodiesel, as replacements for petrol and diesel fuels, respectively, in the transport sector.In Western Australia, there is a potential for replacing diesel fuel consumed in its transport sector by biodiesel produced from rapeseed (canola) grown as one of the break crops between cereal crops. Apart from the availability of raw material, sustainable biodiesel production from rapeseed needs to be analysed from, among other factors, its energy efficiency, which can be determined from the energy ratio of the overall biodiesel production process, defined as the ratio of energy output from biodiesel to the total primary energy consumed during rapeseed growing and processing into biodiesel.In this study, the energy ratio of biodiesel production from rapeseed in Western Australia is evaluated through an energy balance analysis, considering typical Western Australian rapeseed growing practices and rapeseed processing parameters. The energy ratio is then used to evaluate the land, water, and labour requirements of a large scale biodiesel production to analyse its feasibility as a replacement for fossil diesel fuel consumption in Western Australian transport sector. The energy ratio and feasibility of the biodiesel production process are then compared to those of ethanol production from mallee in Western Australia since both biofuels are produced as alternative transport fuels and an assessment is therefore needed to decide which fuel is more feasible to produce, considering the competition for limited resources, e.g. arable land, during their production.Without by-products utilisation, the energy ratio of biodiesel production from rapeseed is found to be less than 1, indicating a negative energy return. The most significant improvement to the energy ratio is achieved when all by-products are utilised, resulting in an energy ratio of 1.70.A feasibility analysis using the net energy approach with an energy ratio of 1.70 shows that the land and labour requirements of a large scale biodiesel production are the major constraints to its realisation as an alternative to diesel fuel in Western Australian transport sector. Replacement of a significant fraction of diesel fuel consumption in the transport sector would cause severe competition for arable land with production of other crops. The net biodiesel production rate is also lower than that required to maintain the current transport activities that are supported by diesel fuel produced by Western Australian energy sector.Feasibility analysis of large scale ethanol production shows, on the other hand, that there is potential to replace approximately 15% of the total petrol fuel consumption in Western Australian transport sector with ethanol produced from mallee grown in Western Australian wheatbelt to tackle dryland salinity problem. The net ethanol production rate would also be sufficient to maintain the current transport activities that are supported by petrol fuel produced by Western Australian energy sector. The feasibility of the large scale ethanol production is, however, dependent on the availability of sufficient water, and hence rainfall, to maintain a consistent mallee yield per hectare of agricultural area.The results of energy balance and feasibility analyses in this study imply that wide implementation of rapeseed-based biodiesel in Western Australia is unsustainable. Possible future implementation should be directed at smaller and more specific targets and should be supported by development of key strategies in both rapeseed growing and rapeseed processing stages aimed at increasing rapeseed yield and reducing main energy input contributors to improve the energy ratio and productivity of the whole production process. The results also show that ethanol production from mallee grown in Western Australian wheatbelt to tackle dryland salinity problem provides an option for a large scale biofuel production to play significant role in future energy security in Western Australian transport sector.